Exploring the role of metabolic pathways in TNBC immunotherapy: insights from single-cell and spatial transcriptomics - Chen, Shi-liang; Fei, Yi-Ran; Cai, Xin-xian; Wang, Cong; Tong, Shi-yuan; Zhang, Zhe-zhong; Huang, Yan-xia; Bian, Dan-dan; He, Yi-bo; Yang, Xiao-xiao (Frontiers in Endocrinology, 2025)
The article provides an overview of the current understanding of the interplay between metabolic pathways and immune function in the context of triple-negative breast cancer (TNBC). It highlights recent advancements in single-cell and spatial transcriptomics technologies, which have revolutionized the analysis of tumor heterogeneity and the immune microenvironment in TNBC. The review emphasizes the crucial role of metabolic reprogramming in modulating immune cell function, discussing how specific metabolic pathways, such as glycolysis, lipid metabolism, and amino acid metabolism, can directly impact the activity and phenotypes of various immune cell populations within the TNBC tumor microenvironment. Furthermore, the article explores the implications of these metabolic-immune interactions for the efficacy of immune checkpoint inhibitor (ICI) therapies in TNBC, suggesting that strategies targeting metabolic pathways may enhance the responsiveness to ICI treatments. Finally, the review outlines future directions and the potential for combination therapies that integrate metabolic modulation with immunotherapeutic approaches, offering promising avenues for improving clinical outcomes for TNBC patients.